Phenomenological model of surface-induced anisotropy in magnetic nanostructures - Leonov, A.A.; Dragunov, I.E.; Roessler, U.K.; Bogdanov, A.N. (Functional Materials, 2008)
A phenomenological theory of surface-induced magnetic anisotropy has been developed to describe inhomogeneous distribution of surface interactions into the depth of nanowires with circular cross-section and spherical nanoparticles. For ellipsoidal nanoparticles and elliptical nanocylinders, by using the Neel's approach the surface uniaxial anisotropy coefficients have been derived as functions of nanostructure size and aspect ratios. The authors have shown that in elongated nanosystems, this specific anisotropy stabilizes homogeneous magnetic states in the system whereas in spherical nanoobjects, it tends to violate the magnetic state homogeneity and to induce specific inhomogeneous distributions of magnetization. In addition, the main peculiarities of magnetization switching processes in ellipsoidal nanoparticles have been investigated.